2021
DOI: 10.3390/jcm11010079
|View full text |Cite
|
Sign up to set email alerts
|

Review: Serum Biomarkers of Lung Fibrosis in Interstitial Pneumonia with Autoimmune Features—What Do We Already Know?

Abstract: Interstitial pneumonia with autoimmune features (IPAF) belongs to a group of diseases called interstitial lung diseases (ILDs), which are disorders of a varied prognosis and course. Finding sufficiently specific and sensitive biomarkers would enable the progression to be predicted, the natural history to be monitored and patients to be stratified according to their treatment. To assess the significance of pulmonary fibrosis biomarkers studied thus far, we searched the PubMed, Medline and Cochrane Library datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The study of biomarkers as additional tools in the clinical practice for the diagnosis and severity of ILD has aroused great interest in the last years [ 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In this regard, the role of ET-1 in the pathogenesis of a large and well-defined cohort of ILD patients remains to be investigated in depth.…”
Section: Discussionmentioning
confidence: 99%
“…The study of biomarkers as additional tools in the clinical practice for the diagnosis and severity of ILD has aroused great interest in the last years [ 17 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In this regard, the role of ET-1 in the pathogenesis of a large and well-defined cohort of ILD patients remains to be investigated in depth.…”
Section: Discussionmentioning
confidence: 99%
“…4 and 5). Both CXCR4 /CXCL12/SDF‐1 (Scotton and Chambers 2007) and CXCL10/IP‐10 (Miądlikowska et al 2021) have been identified as potential biomarkers of pulmonary fibrosis, however neither have been previously linked to the enhanced WT1 expression levels in this disease (Karki et al 2015; Sontake et al 2015). Based on our previous studies (Gonga‐Cavé et al 2021), it is likely that IP‐10 is jointly derived from both DD PFMs and from immune cells in DD.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly the addition of the ve investigational biomarkers SP-A, KL-6, LDH, CRP, and tIgE signi cantly increased the AUC to 0.756 for comparison of Stability AUC -Exacerbation AUC in IPAF cohort (P < 0.05 for the difference between the curves) (Table3, Figure 4). [27,[39][40][41][42][43][44][45][46][47][48][49] Pulmonary function testing (PFT) and Blood cell test Whether IPAF is compared with IPF, or simply a comparison among the three strati cations of the severity of IPAF (p<0.05), apart from DLCO, which identi ed 36 patients with moderate interstitial lung disease, the remaining PFT items, including FVC, FEV1 showed that the patients in two cohorts did not show signi cant clinical signi cance in PFT (Figure 5). No abnormality was found in the selected cytokines in the blood cell test in the IPAF and IPF cohorts.…”
Section: Combinatorial Signaturementioning
confidence: 99%